2013
DOI: 10.1111/psyp.12168
|View full text |Cite
|
Sign up to set email alerts
|

Does exercise induce hypoalgesia through conditioned pain modulation?

Abstract: Pain sensitivity decreases with exercise. The mechanisms that underlie this exercise-induced hypoalgesia (EIH) are unclear. Our purpose was to investigate conditioned pain modulation (CPM) as a potential mechanism of EIH. Sixteen women completed pain testing during three sessions: painful exercise, nonpainful exercise, and quiet rest. Intensity and unpleasantness ratings to noxious heat stimuli were assessed at baseline and during and following each session. Results showed that pain sensitivity decreased signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 41 publications
5
70
1
Order By: Relevance
“…48 Ellingson and colleagues recently tested this hypothesis by examining EIH via painful exercise, nonpainful exercise, and quit rest. 6 The results suggested that while exercise-induced muscle pain may contribute to the magnitude of pain reduction following acute exercise, CPM is likely not the primary mechanism of EIH. Lemely et al tested whether CPM predicts isometric EIH in healthy older and younger adults.…”
Section: Discussionmentioning
confidence: 93%
“…48 Ellingson and colleagues recently tested this hypothesis by examining EIH via painful exercise, nonpainful exercise, and quit rest. 6 The results suggested that while exercise-induced muscle pain may contribute to the magnitude of pain reduction following acute exercise, CPM is likely not the primary mechanism of EIH. Lemely et al tested whether CPM predicts isometric EIH in healthy older and younger adults.…”
Section: Discussionmentioning
confidence: 93%
“…11,19 For example, we have previously shown the magnitude of EIH is related to sedentary behavior across weight status. 4 Future pediatric research is necessary to evaluate other multi-factorial mechanisms such as psychosocial factors as well as specific pain conditions in a variety of ages.…”
Section: Discussionmentioning
confidence: 99%
“…23 Ellingson et al 68 reported a greater hypoalgesic response in 16 pain-free women after painful aerobic exercise compared with nonpainful aerobic exercise, supporting the link between CPM and EIH. The relation between CPM and EIH could indicate similar mechanisms underlying the hypoalgesic response; however, the relation was weak and hypoalgesia has also been observed after nonpainful aerobic exercise, 68 indicating that CPM may work as an additive effect after painful exercise. Pain during exercise was not assessed in the current study to confirm this.…”
Section: Cpmmentioning
confidence: 96%